Learning English through Social Media: Experiences of EFL Student Teachers at One Islamic University in Indonesia - Nova Lingga Pitaloka; Hesti Wahyuni Anggraini; Armilia Sari (Ta'dib: Jurnal Pendidikan Islam, 2021)
Social media use in learning English offers unlimited benefits for English learners as it allows collaboration, communication, and resource sharing among its users. However, there has been little information on EFL student teachers’ lived experiences of using social media for learning English, especially in Islamic University in Indonesia. The aim of this study was to delve EFL student teachers‘ perceived experiences of using social media for learning English. This study employed qualitative inquiry, especially phenomenology. There were 10 pre-service EFL student teachers who voluntarily became participants of the study which were recruited by using purposive sampling. Data collection used interview and documentation. The collected data were analyzed qualitatively with several steps, namely preparing and organizing the data for analysis, exploring and coding the data, building description and themes, representing and reporting qualitative findings, interpreting the findings, and validating the accuracy of the findings. The findings showed that students employed some ways of learning English through social media. This study also provides some implications for future research, students, and educators.